Generation of Retinal Organoids with Mature Rods and Cones from Urine-Derived Human Induced Pluripotent Stem Cells - Guilan Li; Bingbing Xie; Liwen He; Tiancheng Zhou; Guanjie Gao; Shengxu Liu; Guangjin Pan; Jian Ge; Fuhua Peng; Xiufeng Zhong (Hindawi Limited, 2018)
Urine cells, a body trash, have been successfully reprogrammed into human induced pluripotent stem cells (U-hiPSCs) which hold a huge promise in regenerative medicine. However, it is unknown whether or to what extent U-hiPSCs can generate retinal cells so far. With a modified retinal differentiation protocol without addition of retinoic acid (RA), our study revealed that U-hiPSCs were able to differentiate towards retinal fates and form 3D retinal organoids containing laminated neural retina with all retinal cell types located in proper layer as in vivo. More importantly, U-hiPSCs generated highly mature photoreceptors with all subtypes, even red/green cone-rich photoreceptors. Our data indicated that a supplement of RA to culture medium was not necessary for maturation and specification of U-hiPSC-derived photoreceptors at least in the niche of retinal organoids. The success of retinal differentiation with U-hiPSCs provides many opportunities in cell therapy, disease modeling, and drug screening, especially in personalized medicine of retinal diseases since urine cells can be noninvasively collected from patients and their relatives.